(3RgQ GdQHjYs - (3CHh YHO Gddg Rjf GdOjf eMeO Hf CHi HcQ Hf YHO GdbGOQ GdQGRi dMfais; (3CHhHcQ GdQGRj , eMeO Hf RcQjG, CHh HcQ GdQGRj,J (B311 (3g` s ((3eMeO Hf YHOGdQMef RGOI s)
(3ChdgG (B:s
(3gPG eNJUQ LeYJ ajg CMSf eG QCjJg ai cJGH QHjY GdCHQGQ hSejJg RgQ GdQHjY aUd ai JegjO GdYPQ ai LeY gPG GdcJGH s
(3BNQgG (B:s
(3jGQShd Gddg ChUfi ? abGd (B! (3Ydjc HGdHmC eeG ai CjOi GdfGS , hEjGc hGdWeY aEfg abQ MGVQ s
(3cGf GdeDda MjG SfI (B666(3g`s
(3hHBNQ UaMGJgG eWGdYI SfI (B968(3g`s
(3hHChdgG Jedc eDQN ai (B1203 (3g`s
(3hHBNQ UaMGJgG JYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdCOHs